Laminar Profile of Auditory Steady-State Response in the Auditory Cortex of Awake Mice - Li, Zijie; Li, Jinhong; Wang, Shuai; Wang, Xuejiao; Chen, Jingyu; Qin, Ling (Frontiers in Systems Neuroscience, 2021)
Abstract Objective: Auditory steady-state response (ASSR) is a gamma oscillation evoked by periodic auditory stimuli, which is commonly used in clinic electroencephalographic examination to evaluate the neurological functions. Though it has been suggested that auditory cortex is the origins of ASSR, how the laminar architecture of neocortex contributes to the ASSR recorded from the brain surface remains unclear. Methods: We used a 16-channel silicon probe to record the local field potential and the single-unit spike activity in different layers of auditory cortex of unanesthetized mice. Click-trains with a repetition rate at 40-Hz were present as sound stimuli to evoked ASSR. Results: We found that the LFPs of all cortical layers showed a stable ASSR synchronizing to the 40-Hz click stimuli, while the ASSR was the strongest in the granular (thalamorecipient) layer. Furthermore, time-frequency analyses also revealed the strongest coherence between the signals recorded from the granular layer and pial surface. Conclusion: Our results reveal 40-Hz ASSR primarily shows the evoked gamma oscillation of thalamorecipient layers in the neocortex, and the ASSR may be a biomarker to detect the cognitive deficits associated with impaired thalamo-cortical connection.